Branding Bhakti : Krishna Consciousness and the Makeover of a Movement - Karapanagiotis, Nicole (Book collections on Project MUSE., 2021)
"How do religious groups reinvent themselves in order to attract new audiences? How do they rebrand their messages and recast their rituals in order to make their followers more diverse? In Branding Bhakti, Nicole Karapanagiotis considers the new branding of the Hare Krishna Movement, or the International Society for Krishna Consciousness (ISKCON). Known primarily for their orange robes, shaved heads, ecstatic dancing on the streets, and exuberant Hindu-style temple worship, many contemporary ISKCON groups are radically reinventing their public presentation and their style of worship in order to attract a global audience to their movement. Karapanagiotis explores their innovative and complex approaches in both the United States and India by following three new ISKCON brands aimed at gathering new followers. Each is led by a world-renowned ISKCON guru and his global disciples, and each is promoted through a mix of digital and social media and the construction of an innovative "worship-scape." These new spaces trade ISKCON's traditional temples for corporate work-klife balance programs, posh yoga studios, urban spiritual lounges, edgy mantra clubs/lofts, and rural meditative retreat facilities. Branding Bhakti not only investigates the methods the ISKCON movement uses to position itself for growth but also highlights devotees' painful and complicated struggles as they work to transform their shrinking, sectarian movement into one with global religious appeal"--